2011
DOI: 10.3109/02713683.2011.593722
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous Pharmacokinetics and Retinal Safety of Intravitreal Preserved Versus Non-preserved Triamcinolone Acetonide in Rabbit Eyes

Abstract: Following a single intravitreal injection, the median concentration of triamcinolone acetonide is significantly higher in the TA-BA compared to the TA-PF group at 7 days post-injection. No toxic reactions in the retina were observed in either group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…6) of the nanoparticle-within-microparticle drug delivery system was measured to assess the suitability for IVT. The particle sizes were in the range of 3.04 -6.04 µm which is considerably smaller than previously reported particles of sizes 14 -21 μm (9,67) which showed no effects on the retinal in vivo studies. Thus, based on the size, the particles appear to be suitable for IVT.…”
Section: Particle Size and Zeta Potentialmentioning
confidence: 68%
“…6) of the nanoparticle-within-microparticle drug delivery system was measured to assess the suitability for IVT. The particle sizes were in the range of 3.04 -6.04 µm which is considerably smaller than previously reported particles of sizes 14 -21 μm (9,67) which showed no effects on the retinal in vivo studies. Thus, based on the size, the particles appear to be suitable for IVT.…”
Section: Particle Size and Zeta Potentialmentioning
confidence: 68%
“…There have been no prior reports of Naka-Rushton analysis in preclinical studies involving intravitreal administrations of MTX. However, research by Oliveira et al 8 on intravitreal administration of triamcinolone acetonide in normal rabbit eyes reported ''-log K'' values in the range of 2.82-3.37 for both treated and nontreated eyes. The range of ''-log K'' values obtained in the photopic protocol of the current study (2.92-2.97) is similar to that obtained in the study of Oliveira et al 8 Furthermore, the Naka-Rushton analysis showed that there is no significant difference in the means of the ''n'' values and the means of the ''-log K'' values in any of the eyes for both the scotopic and the photopic protocols, which also implies no significant change in the retinal sensitivity because of the presence of the PLAcoated CS-MTX microimplant or the placebo microimplants.…”
Section: Author Disclosure Statementmentioning
confidence: 97%
“…Prior studies that involved assessment of the safety of the intravitreal implants using ERG were involved with sustained administration of lipophilic drugs, such as dexamethasone, triamcinolone, and 2-methoxyestradiol. [6][7][8][9] There has been no report of evaluation of the safety of sustained-release hydrophilic drugs, such as MTX, over a long duration using ERG.…”
Section: Assessment Of Toxicity From Mtx Delivery Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Some in vivo experimental studies suggest that TA intravitreal injection, which formula contains PS80, is safe [10][11][12] . However, other experimental studies suggest that TA formulation without preservative is less toxic to retina after intravitreal injection than most common formulas [13][14][15] .…”
mentioning
confidence: 99%